2010
DOI: 10.1007/s10840-009-9465-9
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmias in patients treated with methadone for opioid dependence

Abstract: Ventricular arrhythmias in patients on methadone are an uncommon but important problem. Buprenorphine, a partial micro-opiate-receptor agonist and a kappa-opiate-receptor antagonist does not cause QTP or TdP. Buprenorphine is a useful and effective alternative to methadone in a select group of patients, including those with documented ventricular arrhythmias on methadone. Pacemakers or defibrillators should be reserved for patients who have failed buprenorphine or a reduced methadone dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 17 publications
4
21
0
Order By: Relevance
“…Differential cardiovascular effects are plausible due to the established risk of QT‐interval prolongation and serious arrhythmia associated with MET 66, 67. Two high ROB OBSs with poorly characterized methods of collecting and analyzing AEs had discordant findings.…”
Section: Discussionmentioning
confidence: 99%
“…Differential cardiovascular effects are plausible due to the established risk of QT‐interval prolongation and serious arrhythmia associated with MET 66, 67. Two high ROB OBSs with poorly characterized methods of collecting and analyzing AEs had discordant findings.…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of opioid addiction, buprenorphine has similar efficacy to moderate doses of methadone but is associated with less QTc interval prolongation, and is one potential alternative. 4,6,28,29,42,56,102 A QTc interval of 450 to 500 ms in adults is also associated with increased risk of torsades de pointes. 47,57,77 Data from general populations of U.S. adults indicate that less than 5% of men and women have QTc intervals of >450 ms. 83,111 Although the risk associated with a QTc interval of 450 to 500 ms is lower than in patients with QTc intervals of >500 ms, the panel recommends that clinicians consider alternatives to methadone because there may be some additional risk.…”
Section: Baseline Electrocardiogramsmentioning
confidence: 99%
“…In addition, clinicians may consider lowering the methadone dose with follow-up to document improvement or normalization of the QTc interval. 28,42,59 For patients treated for opioid addiction who develop a prolonged QTc interval on methadone, buprenorphine is a potential alternative. Buprenorphine has similar efficacy to moderate doses of methadone for treatment of opioid addiction, and observational studies report normalization of prolonged QTc intervals after switching patients from methadone to buprenorphine.…”
Section: Follow-up Electrocardiogramsmentioning
confidence: 99%
See 1 more Smart Citation
“…In-vitro studies by Katchman et al found that LAAM and methadone are unique among opioids in their tendency to block a critical potassium conductance at concentrations approaching those achieved clinically [4]. Subsequent studies have confirmed that methadone can cause TdP and significantly prolongs the QT interval [5][6][7][8][9]. In a prospective investigation of 177 consecutive cases of sudden death, 72 (41%) were found to have detectable methadone on toxicology examination, while only 12 of 177 subjects (7%) had other opioids, suggesting that methadone is associated with a particular propensity for sudden death [10].…”
Section: The Qt Prolongation Phenomenon In Opioid Addiction Therapymentioning
confidence: 99%